Haptoglobin phenotypes distribution among Hemolytic Disease of Newborn (HDN) - Mokhtar, Zeinab Abushar AbdElmotaal; Elemam, Kamal Eltayeb; Ahmed, Hiba BadrEldin Khalil (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Background; Hemolytic disease of the newborn (HDN) is a condition in which transplacentalpassage of maternal antibodies results in immune hemolysis of fetal / neonatal red cells. AHaptoglobin function is to bind free plasma hemoglobin and acute phase reactant protein. Theaim of this study was to determine the frequency of Haptoglobin phenotypes among newbornswith HDN and to explore the Haptoglobin phenotypes in the fetus with HDN according to theirABO group and Rh system. Materials and Methods; A total of 80 patients had HDN wereenrolled in this study; 33 (41.25 %) were females and 47 (58.75%) were males; their age ranged(1-8) days. Haptoglobin phenotypes were identified using polyacrylamide gel electrophoresis(PAGE) method. Discussion and conclusions; A higher frequency of Haptoglobin 1-1   phenotype was observed among newborns with HDN. Both males and females newborns wereshowed high percent of Hp1-1 in distribution. The highest hemoglobin concentration was relatedwith Hp1-1 and the lowest concentration was related to Hp2-2. The highest total white bloodcells count was related to Hp2-1, and this might described that Hp2 subjects were characterizedby a higher immune reactivity. Also we observed the lowest count of RBCs, PCV and indiceswas related to Hp2-2.The most frequent ABO group in patients was O Rh positive. However, itremains unclear the association between the lowest level of direct and indirect bilirubin and Hp2-2 in our study, perhaps to the small data of Hp2-2 phenotype in the study.